Effect of position and pneumoperitoneum on respiratory mechanics and transpulmonary pressure during laparoscopic surgery - Lehavi, Amit; Livshits, Boris; Katz, Yeshayahu (Laparoscopic Surgery, 2018)
Background: Optimizing mechanical ventilation in patients undergoing laparoscopic surgery, often in extreme head up or head down position, requires understanding of the effect of both position and pneumoperitoneum on respiratory mechanics and esophageal pressure—a good surrogate for transpulmonary pressure (TPP) and estimation of optimal positive end expiratory pressure (PEEP). Methods: Esophageal and airway pressures were monitored in 20 patients scheduled for elective laparoscopic surgery during both position changes (15 degrees head up, supine and 15 degrees head down) and increasing degree of pneumoperitoneum (0, 5, 10 and 15 mmHg). Results: Significant increase in peak respiratory pressure, end inspiratory and end expiratory esophageal pressures were noted both in head down position and during increasing pneumoperitoneum pressure. Conclusions: As both ventilation pressures and esophageal pressures significantly change in head down position and during increasing pneumoperitoneum pressure. High PEEP (possibly greater than 10 cm of water) may be required to compensate for the increase in TPP when performing laparoscopic surgery requiring high pressures or extreme head down position.